Rancang Bangun Sistem Kontrol Solenoid Valve dan HMI pada Auto Blowdown Berbasis PLC - Paul Michael Siahaan; Ahmad Zohari; Finnan Erlandung (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
One of the main challenges faced by PT QPR is product failure in the form of under-cured tires during the curing process due to pressure shaping drop. The number of under cure scrap occurring on the TTC 16 curing machine in March 2025 was 9 pieces, which has been analyzed to be caused by the water content in the steam. Therefore, the design and construction of this automatic blowdown system are carried out with the aim of reducing the water content in the steam to decrease undercure scrap and maintain the quality of tire products. The design and development carried out include the addition of a pilot acting solenoid valve integrated with the Mitsubishi Q- Series PLC as an automatic control system, as well as the addition of a button on the Mitsubishi GOT2000 HMI for manual control. The results of the research conducted show that the control system on the automatic blowdown system can operate both automatically and manually effectively. The reduction in the number of under-cure scrap on the TTC 16 machine also occurred after the design and construction of the automatic blowdown system, amounting to 6 pieces over a period of 28 days.